Nitrogen migration in products during the microwave-assisted hydrothermal carbonization of spirulina platensis. (May 2022) - Guo, Dandan; Wang, Yuang; Gao, Ying; Lyu, Yinong; Lin, Yunhao; Pan, Yueshen; Zhu, Lin; Zhu, Yuezhao
Graphical abstract: Highlights: The nitrogen migration of Spirulina platensis during MHTC was investigated. The hydrochar was rich in pyridininc-N, protein-N, pyrrolic-N and quaternary-N. The liquid product contained large amounts of NH4 + -N, NO3 – -N and organic-N. The photoluminescence properties of CDs correlated with the N-containing species. The transformation mechanism of nitrogen was proposed. Abstract: Nitrogen has a vital influence on the properties of the microwave-assisted hydrothermal carbonization (MHTC) products of Spirulina platensis (SP). The effects of hydrothermal temperature (140–220 °C) and time (1–4 h) on the product distribution and nitrogen migration of SP in MHTC were studied. Increasing temperature led to an increase in the carbon content, and a decrease in the nitrogen content in hydrochar. Protein-N was the major nitrogen-containing species in hydrochar. The total nitrogen in liquid phase increased significantly with increasing temperature. Carbon dots were found to be one of the valuable products in the liquid phase. Higher temperatures improved the amine-N level and reduced the quaternary-N content in carbon dots. A close correspondence was found between the N-containing species and the luminescence centers of carbon dots. A possible nitrogen migration mechanism was proposed to provide guidance for the potential application of the products.